The shape of things : a philosophy of design - Flusser, Vilém (London : Reaktion Books, 1999)
Introduction by Martin Pawley About the Word Design Form and Material War and the State of Things About Forms and Formulae The Designer's Way of Seeing The Factory The Lever Strikes Back Shelters, Screens and Tents Design: Obstacle for/to the Removal of Obstacles Why Do Typewriters Go 'Click'? The Ethics of Industrial Design? Design as Theology Wittgenstein's Architecture Bare Walls With As Many Holes As a Swiss Cheese The Non-Thing The Non-Thing Carpets Pots Shamans and Dancers with Masks The Submarine Wheels Biographical Note
boek